Kajian Pola Makan Vegetarian Dari Perspektif Makanan Satwika Dalam Ajaran Hindu - Luh Sukarti, Ni; Nyoman Sugi Widiastithi, Ni; Lila Murti, Ketut (Shofanah Media Berkah, 2024)
Food is a primary need for human life and an essential requirement for all living beings to survive, as it serves as a fundamental energy source to perform daily activities. Some individuals adopt a vegetarian diet, avoiding foods derived from animals such as meat, eggs, fish, and other animal-based products. In Hinduism, the concept of Satwika food emphasizes the importance of food not only in fulfilling physical needs but also in contributing to physical, mental, and spiritual balance. However, individuals who follow a vegetarian diet often face health challenges, such as joint pain and prolonged recovery times when ill. Addressing these issues, this study explores vegetarian diets from the perspective of Satwika food in Hinduism. This qualitative research employs a descriptive design, combining library and field studies. Using a phenomenological approach, data were collected through interviews, observations, and documentation studies. The analysis concludes that a vegetarian diet must adhere to the criteria of Satwika food as prescribed in Hindu teachings to ensure not only physical health but also the spiritual and mental well-being of individuals.